2019
DOI: 10.1186/s13046-019-1448-9
|View full text |Cite
|
Sign up to set email alerts
|

NOS1 inhibits the interferon response of cancer cells by S-nitrosylation of HDAC2

Abstract: BackgroundThe dysfunction of type I interferon (IFN) signaling is an important mechanism of immune escape and metastasis in tumors. Increased NOS1 expression has been detected in melanoma, which correlated with dysfunctional IFN signaling and poor response to immunotherapy, but the specific mechanism has not been determined. In this study, we investigated the regulation of NOS1 on the interferon response and clarified the relevant molecular mechanisms.MethodsAfter stable transfection of A375 cells with NOS1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…These results suggested that NOS1 may be involved in chemoresistance. Indeed, NOS1 expression enhanced chemoresistance to cis-diamminedichloroplatinum (cisplatin/DDP) in ovarian cancer and inhibited the interferon response of lung cancer cells [ 52 54 ]. Thus, NOS1 plays a role in therapy resistance and might be a modulator of therapeutic improvements through the regulation of cancer-associated macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that NOS1 may be involved in chemoresistance. Indeed, NOS1 expression enhanced chemoresistance to cis-diamminedichloroplatinum (cisplatin/DDP) in ovarian cancer and inhibited the interferon response of lung cancer cells [ 52 54 ]. Thus, NOS1 plays a role in therapy resistance and might be a modulator of therapeutic improvements through the regulation of cancer-associated macrophage polarization.…”
Section: Discussionmentioning
confidence: 99%
“…We identified one high-confidence interaction of wild-type Nsp5 with the epigenetic regulator histone deacetylase 2 (HDAC2), and predicted a cleavage site between the HDAC domain and the nuclear localization sequence ( Extended Data Fig. 6a - d ), suggesting that Nsp5 may inhibit HDAC2 transport into the nucleus, potentially impacting HDAC2’s mediation of inflammation and interferon response 22 , 23 . We also identified an interaction of catalytically dead Nsp5 (C145A) with tRNA methyltransferase 1 (TRMT1), which is responsible for the dimethylation of guanosine (m2,2G) on both nuclear and mitochondrial tRNAs 24 .…”
Section: Mainmentioning
confidence: 99%
“…For wild-type Nsp5, we identified one high-confidence interaction, the epigenetic regulator histone deacetylase 2 (HDAC2), and predicted a cleavage site between the HDAC domain and the nuclear localization sequence, suggesting that Nsp5 may inhibit HDAC2 transport into the nucleus (Extended Data Fig. 7), potentially impacting the published functions of HDAC2 in mediating inflammation and interferon response 38,39 . We also identified an interaction of Nsp5 (C145A) with tRNA methyltransferase 1 (TRMT1), which is responsible for synthesis of the dimethylguanosine (m2,2G) base modification on both nuclear and mitochondrial tRNAs 40 .…”
Section: The Sars-cov-2 Interactome Reveals Novel Aspects Of Sars-covmentioning
confidence: 99%